(untitled) (Modern education and development, 2025)
This article analyzes the main models of knowledge presentation and their application. In connection with the development of educational methods and technologies, the importance of various models for the effective presentation of knowledge in the educational process is increasing. The article considers such models as traditional education, distance learning, blended learning (hybrid learning), experiential learning, constructivism, goal-oriented learning, project-based learning, and gamification. The article provides a comparative analysis of new approaches and methods in education, which are important in creating opportunities for students to acquire modern knowledge.